Applied Water Science - Aljlil, Saad A.; Macedonio, Francesca; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
Applied Water Science is an open access journal that explores water scarcity solutions from a holistic system oriented viewpoint. It focuses on the sustainable management of natural water resources to the development of the technologies and infrastructure for the production of clean fresh water from natural and waste water. It accepts innovative and sound theoretical research on different water issues, exploring potential alternative water sources via recycling and reuse of wastewater with a focus on arid and semiarid environments and the following topics; water desalination, drinking water treatment, wastewater treatment, water resources planning, investigation and management. Applied Water Science is committed to upholding the integrity of the scientific record. As a member of the Committee on Publication Ethics (COPE) the journal will follow the COPE guidelines on how to deal with potential acts of misconduct. Authors should refrain from misrepresenting research results which could damage the trust in the journal and ultimately the entire scientific endeavor. Maintaining integrity of the research and its presentation can be achieved by following the rules of good scientific practice as detailed here: https://www.springer.com/us/editorial-policies .
Keywords: Geology; Water; Hydrology; Industrial engineering; Production engineering; Pollution; Nanotechnology; Private international law; Conflict of laws; International law; Comparative law; Geology; Water; Industrial and Production Engineering; Pollution; Nanotechnology; Private International Law, International and Foreign Law, Comparative Law